Biologia reprodutiva de Hypsiboas lundii (Anura, Hylidae) em um fragmento de Cerrado no sudoeste de Minas Gerais - Mazzarelli, Cilene Cristina Mathias [UNESP] (2015)
Currently, approximately 7390 amphibian species are known in the world, with a great diversity in Brazil: 1026 amphibians, of which 988 are anuran species. Distribution and reproduction of species are greatly influenced by local climatic conditions. In the seasonal tropics, species exhibit a temporal reproductive pattern more associated to the rainy season, while in more stable regions, such as tropical rain forests, reproduction is more influenced by the temperature. Anuran species adopt a variety of strategies to maximize reproductive success, which are related to the temporal reproductive pattern. Explosive species reproduce in a short period of time, and competition among males is more intense compared to prolonged breeding species. Moreover, anurans commonly change strategies according to social contexts, such as aggressive interactions or courtship, which may involve many stimuli types, such as acoustic, tactile, chemical and visual. The present study was conducted in the Cerrado, a formation composed by many different types of phytophysiognomies, from grassfields to forests. We describe the reproductive biology of the hylid frog Hypsiboas lundii, a species widely distributed throughout the Cerrado with a life cycle associated to streams. Observations were monthly between Oct/2013 and Jan/2015, in the municipality of Sacramento, Minas Gerais state. The species exhibited a prolonged reproductive pattern, with males calling from Oct/2013 to May/2014, and in Dec/2014 and Jan/2015, predominantly from the ground. Courtship behavior was complex, involving acoustic and tactile signals. Clutches were deposited mainly in depressions at the stream banks, which were previously inspected by females and, after amplexus, enhanced by them. Aggressive interactions involved territorial call emission and vocal duels. We also describe advertisement, courtship and territorial calls, which were mainly differentiated by note duration and intensity